Ответ(ы) на вопрос:
3) y=1; y' = 0
4) [latex]y= \sqrt[4]{x} [/latex]; y' = [latex] \frac{1}{4} x^{ -\frac{3}{4} } = \frac{1}{ 4 x^{\frac{3}{4}}}[/latex]
5) y=x; y' = 1
6) y=x³; y' = 3x²
7) y=[latex]10 x^{8} +5 x^{ \frac{6}{7} } [/latex]; y' = [latex]80 x^{7} + \frac{30}{7} x^{- \frac{1}{7} } =80 x^{7} + \frac{30}{7 \sqrt[7]{x} }[/latex]
8) [latex]y=8 \sqrt{x} +3 \sqrt[5]{x} [/latex]; y' = [latex]4 \frac{1}{ \sqrt{x}} +\frac{3}{5} x^{- \frac{4}{5} } =\frac{4}{ \sqrt{x}} +\frac{3}{5 x^{\frac{4}{5}}}[/latex]
9) [latex]y=- \sqrt[5]{x} -7 \sqrt[10]{x} [/latex]; y' = [latex]- \frac{1}{5} x^{- \frac{4}{5} } - \frac{7}{10}x^{ -\frac{9}{10} }=- \frac{1}{5 x^{\frac{4}{5} } } - \frac{7}{10x^{\frac{9}{10} }}[/latex]
10) y=[latex]2 x^{ \frac{5}{6} } -3x^7[/latex]; y' = [latex]\frac{2*5}{6} x^{ -\frac{1}{6} } -21x^6= \frac{5}{3 \sqrt[6]{x}} -21x^6[/latex]
11) y=-5x³-tgx; y' = -15x²-(tg²x+1) = [latex]-15 x^{2} - \frac{1}{cos^2x} [/latex]
Не нашли ответ?
Похожие вопросы